2015
DOI: 10.1007/s00246-015-1162-0
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, Low-Grade Inflammation and Cardiovascular Risk in Young Children: A Pilot Study

Abstract: Vitamin D has anti-inflammatory properties, and deficiency is prevalent in children. There is a paucity of data regarding vitamin D status and its correlation with low-grade inflammation and vasculature. We prospectively enrolled 25 children, 9-11 years old (13 male); 21 obese. Eight atherosclerosis-promoting risk factors were scored as categorical variables with the following thresholds defining abnormality: body mass index Z score ≥ 1.5; systolic blood pressure ≥ 95th percentile (for age, sex, and height); t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…Similarly, van de Luijtgaarden et al [41] showed that low vitamin D status was associated with higher CIMT. Our findings are in contrast with recent studies [42][43][44][45][46] that demonstrated there was no association between vitamin D level and CIMT. There are several possible explanations for discrepancy in findings of the studies including differences in vitamin D dosage of supplementation and serum level of vitamin D, differences in study design, different methods of CIMT measurement and the various populations (healthy vs. unhealthy subjects and adult vs. children).…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, van de Luijtgaarden et al [41] showed that low vitamin D status was associated with higher CIMT. Our findings are in contrast with recent studies [42][43][44][45][46] that demonstrated there was no association between vitamin D level and CIMT. There are several possible explanations for discrepancy in findings of the studies including differences in vitamin D dosage of supplementation and serum level of vitamin D, differences in study design, different methods of CIMT measurement and the various populations (healthy vs. unhealthy subjects and adult vs. children).…”
Section: Discussioncontrasting
confidence: 99%
“…Vitamin D has been shown to inhibit inflammatory reactions, which can affect the function of many organs, including organs in the cardiovascular and vascular systems [7-11]. Furthermore, vitamin D deficiency has been identified as a risk factor for myocardial infarction, heart failure, and inflammatory cardiovascular disease [12-14].…”
Section: Introductionmentioning
confidence: 99%
“…For c-IMT measurement, the proximal part of the carotid bulb of the right carotid artery was identified, and the closest 1 to 2 cm segment of the common carotid artery was scanned (20). The c-IMT was identified 10 mm below the distal wall of the common carotid artery, within 2 cm of the carotid bifurcation (21). All measurements were made by the same radiologist, who was unaware of the participants' 25(OH)D levels.…”
Section: Methodsmentioning
confidence: 99%